A cost–benefit analysis for the institutionalization of the green certification scheme: the case of the development of the Sinjung district in Seoul, Korea. Issue 1 (2nd January 2016) - Lee, Min Gi; Kim, Hong Bae
Abstract : Recently, Kim and Park [2014. The structure of the green certification scheme for the neighborhood and application to newtown development: The case of Magok, Seoul, Korea. International Journal of Urban Sciences, 18 ] presented a green certification scheme that is applicable to neighbourhood units and demonstrated that it is an effective means to achieve low-carbon cities in Korea. However, in order for this scheme to be formally institutionalized, it must be shown that public welfare will be positively affected. This is because the implementation of the scheme becomes meaningful only when it improves people's welfare. Hence, this paper conducted a cost–benefit analysis for the institutionalization of the green certification scheme through the following four steps: First, the effects of the costs and benefits caused by the scheme were itemized. Second, valuation methods for the itemized effects were presented. Third, those effects were specifically measured while focusing on the development of the Sinjung district, which is a typical case for neighbourhood development in Seoul, Korea. Finally, in the fourth step, the scheme was evaluated based on the total costs and benefits.